Green building A to Z : understanding the language of green building - Yudelson, Jerry (New Society Publshers, 2007)
Offers the basics of green building and shows how it relates to key issues such as, water conservation, healthy buildings, use of recycled materials, reduction of carbon dioxide, and environmental site planning.